Effect of poly(amic acid) imidization on solution characteristics and membrane morphology - Lee, HJ; Won, J; Park, HC; Lee, H; Kang, YS (ELSEVIER SCIENCE BV, 2000)
The imidization effect of a poly(amic acid) dope solution on membrane formation has been investigated. Poly(amic acid) solution in N-methyl-2-pyrrolidione has been thermally imidized at 120 degrees C at different curing times. The degree of imidization was determined by infrared spectroscopy. The solution properties have been studied as a function of concentration and curing time by dynamic light scattering. The quality of a solvent changed from good to poor with increasing imidization of poly(amic acid). The reduced polymer-solvent interaction diminishes the membrane formation time. The morphology of a membrane was able to be controlled by the characteristics of the dope solution. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: SEPARATION; ACETATE; AIR